Analisis Mikrobiologi Bekasam Ikan: Pengamatan dan Identifikasi Bakteri Menggunakan Teknik Pewarnaan Violet Safranin dan Iodine - Khusnul Khotimah Rijie; Ardi Mustakim (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2025)
Fish bekasam is one of Indonesia's traditional fermented products that involves the activity of microorganisms, especially lactic acid bacteria (LAB), to produce unique organoleptic, chemical, and microbiological characteristics. The fermentation process of bekasam plays a significant role not only in extending the shelf life of fish but also in creating a distinctive sour taste and texture that differs from other fish products. This study aims to analyze the microbiological community involved in the fish bekasam fermentation process through observation and identification of bacteria using Safranin Violet and Iodine staining techniques. This study employs a literature review approach, examining various references related to the fermentation process, the dominant bacteria species, and the environmental factors that affect the quality of bekasam. The analysis revealed that lactic acid bacteria such as Lactobacillus plantarum, Lactobacillus casei, and Pediococcus spp. play an important role in the fermentation of bekasam fish. These bacteria produce lactic acid, which contributes to the sour taste and plays a role in forming the product's texture. The Safranin Violet and Iodine staining techniques were effective for identifying bacteria based on their cell wall characteristics, with Gram-positive bacteria dominating the fermentation process. Environmental factors such as the fermentation time, salt concentration, and the addition of ingredients like carbohydrates or turmeric extract influence the dynamics of bacterial populations in the fermentation of bekasam. This study also emphasizes the importance of controlling pathogenic bacterial contamination, such as Salmonella spp. and Escherichia coli, to ensure food safety in bekasam products. The findings provide a deeper understanding of the microbiological dynamics in fish bekasam fermentation and the relevance of staining techniques in microbiological analysis, which can be used to improve the quality and safety of traditional fermented products. This study also opens opportunities for developing safer and higher-quality bekasam products.